Fabrication of Reduced Graphene Oxide Based Ultra–high Cycle Life Flexible Fiber Supercapacitor with Different Modes. Issue 20 (9th December 2016) - Sankar, K. Vijaya; Kumar, N. Rajeesh; Lee, Y. S.; Selvan, R. Kalai
Abstract: Few layered flexible oxygen functionalized reduced graphene oxide (OFRGO) is prepared by hydrothermal method, where Na2 S is acted as reducing agent. The prepared OFRGO is used as electrodes for the fabrication of flexible fiber supercapacitor at various modes like normal, ring and zigzag. The fabricated device exhibits a maximum specific capacitance of 7.6 mF cm −1 at 5 mV s −1 and delivered 97.3 % of Coulombic efficiency over 1.6 lakh cycles. Interestingly, no significant difference in performance is noticed in all the devices that reveals the good flexibility of the device. The available oxygen functional groups support to improve the specific capacitance. Finally, the fabricated symmetric fiber supercapacitor is integrated with energy harvesting system, i. e., commercial solar cells and powered to glow red light emitting diode (LED). Hence, the fabricated flexible device is reliable to integrate with energy harvesting system and can also be used for flexible energy storage applications. Abstract : The oxygen functionalized reduced graphene oxide was prepared by hydrothermal method and used as the electrodes for the fabrication of flexible fiber supercapacitor. The devices were fabricated in different modes like normal, ring and zig‐zag. The fabricated device exhibits the maximum specific capacitance of 7.6 mF cm −1 at 5 mV s −1 and showed 97.3 % Coulombic efficiency over 1.6 Lakh cycles.